2021
DOI: 10.3390/diagnostics11071227
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-Targeted Multispectral Optoacoustic Tomography and Fluorescence Molecular Imaging in Human Carotid Atherosclerotic Plaques

Abstract: Vulnerable atherosclerotic carotid plaques are prone to rupture, resulting in ischemic strokes. In contrast to radiological imaging techniques, molecular imaging techniques have the potential to assess plaque vulnerability by visualizing diseases-specific biomarkers. A risk factor for rupture is intra-plaque neovascularization, which is characterized by overexpression of vascular endothelial growth factor-A (VEGF-A). Here, we study if administration of bevacizumab-800CW, a near-infrared tracer targeting VEGF-A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A subsequent study investigated the utility of MSOT in five patients that received a low-intravenous dose of bevacizumab-800CW. Although the bevacizumab-800CW signal could not be detected with MSOT, in vivo and ex vivo NIRF imaging of the excised plaques correlated with histopathology [ 107 ]. Plaques incubated with scVEGF/Cy5.5 were imaged ex vivo [ 105 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent study investigated the utility of MSOT in five patients that received a low-intravenous dose of bevacizumab-800CW. Although the bevacizumab-800CW signal could not be detected with MSOT, in vivo and ex vivo NIRF imaging of the excised plaques correlated with histopathology [ 107 ]. Plaques incubated with scVEGF/Cy5.5 were imaged ex vivo [ 105 ].…”
Section: Resultsmentioning
confidence: 99%
“…areas displaying high uptake and low uptake, respectively) could be distinguished. Three studies focussed on the angiogenic pathway related to the vulnerable plaque, namely bevacizumab-800CW targeting VEGF-A (two studies) and scVEGF/ Cy5.5 targeting the VEGF-receptor (one study) (Table 2) [105][106][107]. Bevacizumab-800CW was investigated with ex vivo NIRF imaging, showing a clear uptake in plaques retrieved from patients with recent ischemic events, whereas plaques retrieved from older ischemic events did not display strong fluorescent signals.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…In another study (45), the co-registered structural US data, which were recorded along with MSOT, were used to improve the optoacoustic images by reducing limited-view artifacts and increasing contrast. More specifically, the carotid artery lumen and plaque areas were segmented in the US images from three healthy volunteers and five patients with asymptomatic carotid atherosclerosis.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…More specifically, the carotid artery lumen and plaque areas were segmented in the US images from three healthy volunteers and five patients with asymptomatic carotid atherosclerosis. Then, the segmentation masks were used as USbased priors to improve the reconstruction of several optoacoustic frames, including the frames acquired at the 930 nm, where the lipids absorb the most at the NIR of 700-1,000 nm (45). The results showed that the prior-integrated reconstruction rendered the differentiation of the two groups (healthy vs. patients) statistically significant in contrast to the standard reconstruction regime, when based on the optoacoustic signal intensities recorded at 930 nm.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Multiple commercially available open-air NIRF camera systems can detect IRDye800CW (absorption: ~780 nm, excitation: ~800 nm [11,12]), but are primarily intended for ICG (absorption: ~800 nm, excitation: ~830 nm [13]) and cannot be used for minimally invasive surgery [14]. Bevacizumab-800CW is a tumour-targeted tracer, aimed at vascular endothelial growth factor α (VEGFα), which has been used in multiple clinical studies [9,[15][16][17][18][19][20][21][22]. Likewise, cetuximab-800CW, aimed at endothelial growth factor, is used in multiple clinical trials [23,24], and various other antibodies conjugated to IRDye800CW are currently investigated [25][26][27] since the process of developing these tracers is relatively simple compared to developing a new investigational drug or tracer [27,28].…”
Section: Introductionmentioning
confidence: 99%